Macrophage cell lines use CD81 in cell growth regulation - Mordica, Whitney J.; Woods, Keith M.; Clem, Rollie J.; Passarelli, A. Lorena; Chapes, Stephen K. (My University, 2012)
CD81 is an integral membrane protein belonging to the tetraspanin superfamily. It has two extracellular domains that interact with cell surface proteins and two intracellular tails that contribute to cellular processes. Although there are considerable data about how CD81 affects T- and B-cell function, not much is known about how it impacts macrophages. To address this, we established four cell lines from mouse bone marrow in the presence of macrophage colony-stimulating factor and transfection with SV40 large T antigen. Two were CD81[superscript]−/− (ASD1 and ASD2) and two were CD81[superscript]+/− (2ASD1.10 and 2BSD1.10). Cells were Mac-2-, PU.1-, and c-fms-positive and all the cell lines were phagocytic indicating that they were macrophage-like. In mixtures of the two cell types in tissue culture, CD81[superscript]−/− cells out competed CD81[superscript]+/− cells with CD81-bearing cells being undetectable after 50 cell culture passages. Although cell divisions during log-phase growth were not significantly different between CD81[superscript]+/− macrophage cells and CD81[superscript]−/− macrophage cells, we found that CD81[superscript]−/− macrophage cells reached a higher density at confluency than CD81[superscript]+/− macrophage cells. CD81 transcript levels increased as cultures became confluent, but transcript levels of other tetraspanin-related molecules remained relatively constant. Transfection of CD81 into ASD1 (CD81[superscript]−/−) cells reduced the density of confluent cultures of transformants compared to cells transfected with vector alone. These data suggest that CD81 potentially plays a role in macrophage cell line growth regulation.
Keywords: Monocytes/macrophages; Cell surface molecules; Cell proliferation; CD81